2019
DOI: 10.25222/larr.142
|View full text |Cite
|
Sign up to set email alerts
|

Bureaucratic Politicization, Partisan Attachments, and the Limits of Public Agency Legitimacy: The Venezuelan Armed Forces under Chavismo

Abstract: Which factors determine support for the armed forces? What is the effect of agency politicization on confidence? Existing studies, which draw largely from bureaucratically neutral militaries, find that interpersonal trust and demographic variables play significant roles in determining public confidence in the armed forces. I argue that this is different for a politicized agency. A loss of bureaucratic neutrality activates voters’ partisan attachments, inducing individuals to judge the agency on the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Victim of crime in the last 12 months is a dummy variable coded yes and no , while the variable measuring one's fear of being a homicide victim is coded one for “A lot of fear,” two for “Some fear,” three for “Little fear,” and four for “No fear at all.” Moreover, ideology is coded one for left and ten for right . I did not recode the ideology variable, which is consistent with other scholars in the discipline (Polga‐Hecimovich, 2019), since coding the variables left and right misses people who are in the ideological center. Finally, trust in the national police is from one, “Not at all,” to seven, which represents “A lot.” I controlled for trust in the police as a proxy variable for trust in government institutions .…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…Victim of crime in the last 12 months is a dummy variable coded yes and no , while the variable measuring one's fear of being a homicide victim is coded one for “A lot of fear,” two for “Some fear,” three for “Little fear,” and four for “No fear at all.” Moreover, ideology is coded one for left and ten for right . I did not recode the ideology variable, which is consistent with other scholars in the discipline (Polga‐Hecimovich, 2019), since coding the variables left and right misses people who are in the ideological center. Finally, trust in the national police is from one, “Not at all,” to seven, which represents “A lot.” I controlled for trust in the police as a proxy variable for trust in government institutions .…”
Section: Methodsmentioning
confidence: 78%
“…It was suggested that I place four in this first grouping and run the model both ways, but it is important to note that there is not a theoretical or empirical foundation for where to code four on a 7‐point scale. Scholars discuss the advantages and disadvantages of collapsing variables (Murad et al, 2003; Pohlman & Leitner, 2003).…”
mentioning
confidence: 99%
“…However, their use has mushroomed in recent decades, particularly in Latin America. We found evidence of the recent invention or adaptation of qualifiers such as "soft" (Pitts et al, 2016), "parliamentary" (Santos and Guarneri, 2016), "presidential" or "democratic" (Varol, 2017), "constitutional" (Helmke, 2017;Yarwood, 2016), "market" or "neo-liberal" (Mauceri, 1995), "electoral" (Hellinger, 2005), "slowmotion" (Polga Hecimovich et al, 2017), "civil society" (Encarnación, 2002), and "judicial" (Yavuz and Koç, 2016). Many of these terms are piled together in Gentili's (2016) volume on the impeachment of President Dilma Rousseff in Brazil.…”
Section: Introductionmentioning
confidence: 87%
“…This line of argument also stresses some structural features, such as dependence on oil revenues as an explanation (Buxton 2019) rather than policy decisions and transformations undergone during the Bolivarian Revolution led first by Hugo Chávez and later by Nicolás Maduro. On the other hand, institutionalist and liberal scholars see the crisis mainly as a result of the deterioration of governance mechanisms that have undermined checks and balances, the independence of institutions and ultimately turned the country unto an autocracy (Polga-Hecimovich 2019;López Maya 2016).…”
Section: Introductionmentioning
confidence: 99%